Răspuns :
f•g=3(2x+a)+2=6x+3a+2
g•f=2(3x+2)+a=6x+4+a
6x+3a+2= 6x+4+a
3a+2=4+a
3a-a=4-2
2a=2
a=1
g•f=2(3x+2)+a=6x+4+a
6x+3a+2= 6x+4+a
3a+2=4+a
3a-a=4-2
2a=2
a=1
f°g=f(g(x)=f(2x+a) =3(2x+a)+2=6x+3a+2
g°f=g(f(x))=g(3x+2)=2(3x+2)+a=6x+a+4
6x+3a+2=6x+a+4
3a+2=a+4
2a=2
a=1
verificare
f(x) =3x+2
g(x)=2x+1
f°g=3(2x+1)+2=6x+5
g°f=2(3x+2)+1=6x+5
adevarat , bine rezolvat
g°f=g(f(x))=g(3x+2)=2(3x+2)+a=6x+a+4
6x+3a+2=6x+a+4
3a+2=a+4
2a=2
a=1
verificare
f(x) =3x+2
g(x)=2x+1
f°g=3(2x+1)+2=6x+5
g°f=2(3x+2)+1=6x+5
adevarat , bine rezolvat